RADIOGRAPHY OF THE LUMBAL VERTEBRAE COLUMNA WITH SUSPECTED SCOLIOSIS AT BHAYANGKARA HOSPITAL 2nd Grade Medan - Liberti Tarigan; Justinus Tambunan (Journal of Public Health Science, 2025)
The vertebral column is the main pillar of the body's bones that supports the head, upper extremities, and chest cavity. One of the abnormalities in the thoracolumbar vertebrae is Scoliosis. Scoliosis is a deformity of the spine to the lateral side that is excessive in the vertebrae. The effects of Scoliosis will be clearly visible if this disease attacks the lumbar region and causes the pelvis to tilt which impacts the lower extremities so that the patient limps or cannot balance when walking. Scoliosis examination is carried out using several projections, namely Anteroposterior (AP) for supine patients or Posteroanterior (PA) for erect patients is more recommended, Lateral with an erect position, and (AP) bending right and left. This examination was carried out at Bhayangkara TK II Medan in May 2025 with observation and interviews, through image processing using Computer Radiography (CR). The X-ray machine used in the implementation of Lumbar Vertebrae column radiography with suspected Scoliosis is a type of machine with a capacity of 500 mA, but researchers chose a large focus of 200 mA to obtain optimal image sharpness. Because the object being examined is relatively large, it is best to use a grid for image contrast (200 mA).